Development of Synthetic Unit Hydrograph Model in Java Island with Morphometric Parameters - Maulida Hayati; Limantara, Lily Montarcih; Prasetyorini, Linda (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2025)
The synthetic unit hydrograph (HSS) is used as a predictive tool in hydrological studies, particularly to estimate the peak discharge due to design rainfall, which is very useful in water infrastructure planning and flood control. This study aims to develop more accurate HSS parameters by considering the influence of morphometry, namely, the watershed form factor and the watershed area. The study involved 10 watersheds located on the island of Java, which were selected as study sites to provide a broader and more representative context for the variation in characteristics in the study area. The methods used include watershed morphometric analysis to determine the location and shape factor of the watershed, hydrograph analysis to produce unit hydrographs per watershed/sub-watersheds, and hydrograph analysis to determine the size of the sub-watershed and explicit modeling technique with multiple linear regression, which is the writing of a mathematical model that shows the relationship between the dependent variables (Qp and Tp) and the independent variables (A and FD, respectively). The result of the study is a HSS model on Java Island with parameters FD and A obtained the following equation: peak discharge (Qp) = 18.465 - 25.730 (FD) + 0.039 (A), and peak time (Tp) = 2.962 - 0.766 (FD) + 0.001 (A), where FD is the watershed form factor and A is the watershed area. Correlation coefficient (R) for peak discharge (R = 0.962) and peak time (R = 0.974). Coefficient of determination (R2) for peak discharge (R2 = 0.926) and peak time (R2 = 0.948).